Kebijakan Pencatatan Perkawinan Beda Agama - Itok Dwi Kurniawan; Hanuring Ayu; Suyatno Suyatno (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
Marriage is the most awaited thing, especially for couples who will continue their relationship to a more serious level. However, interfaith marriage in Indonesia is something that is difficult to do, there are even some groups who disagree on the issue of interfaith marriage. This is not in accordance with the values of Human Rights, especially regarding the values of family and religious freedom. Of course this is not in accordance with the values contained in the constitution, as we know that Indonesia is a country that upholds the value of human rights. This type of research is library research, that is by browsing books or sources related to the chosen topic.